Morphological evidence from immature stages further suggests Lignyodina being close to Tychiina (Coleoptera, Curculionidae, Curculioninae, Tychiini) - Gosik, Rafał; Skuhrovec, Jiří; Toševski, Ivo; Caldara, Roberto (Zootaxa, 2017)
The relationship between the subtribes Lignyodina and Tychiina of the Tychiini were tested on the basis of morphological characters from the immature stages. The mature larvae of Lignyodes bischoffi (Blatchley, 1916) and L. enucleator (Panzer, 1798) (Curculionidae, Curculioninae, Tychiini, Lignyodina) and the pupae of L. bischoffi are described in detail for the first time. To be sure about the correct taxonomic identification of the larvae, DNA sequences were obtained and compared for both the larvae and adults of these two species. Molecular data show that the two studied species of Lignyodes  Dejean, 1835 strongly differ in mitochondrial COI and 16S rRNA. The immature stages (larva and pupa) of Lignyodes bischoffi and L. enucleator were compared with each other and with those known for other taxa representative of the tribe Tychiini and other tribes of Curculioninae. The larvae of Lignyodes bischoffi and L. enucleator differ in a few but important characters. The larvae and pupae of these two species belonging to Lignyodes s. str. are morphologically very similar to those of species in the other two subgenera of Lignyodes, Neotylopterus Clark, Whitehead & Warner, 1977 and Chionanthobius Pierce, 1912. On the basis of the detailed morphology of larvae and pupae, we agree that Lignyodes belong to Tychiini, sharing more features with species of this tribe than with those of other tribes of Curculioninae. New bionomic data concerning larval and pupal development and adult emergence are reported for both described species and confirm close relationships between the subtribes Lignyodina and Tychiina. On the other hand, strong molecular differences, corroborated by some relevant larval differences, between L. enucleator and L. bischoffi open up the issue whether Palaearctic and Nearctic species presently included in Lignyodes s. str. actually belong to the same subgenus.